A First Step, a Second Chance: Public Support for Restoring Rights of Individuals with Prior Convictions - Mancini, Christina (International journal of offender therapy and comparative criminology, 2021)
Recent federal and state-level justice reforms have centered on “legal reintegration” (e.g., permitting expungement for a greater range of crimes and rights restoration). While scholarship has tapped public opinion of this approach, much of it predates recent reentry efforts. We see an opportunity to extend this literature by focusing on a contemporary sample (N = 374) of residents living in Virginia, a state that recently considered such reforms. Results suggest most of the public supports expungement reform, but less than 40% support rights restoration generally, with approval levels dependent on specific type of restoration. Divides are explained by socio-demographic factors, particularly political ideology and race, as well as crime-related views. Implications are discussed.